Computer Numerical Controlled Grinding and Physical Vapor Deposition for Fused Deposition Modelled Workpieces. (1st November 2018) - Lavecchia, Fulvio; Percoco, Gianluca; Pei, Eujin; Galantucci, Luigi Maria
Abstract : The use of additive manufacturing (AM) enables companies to directly produce complex end-use parts. Fused deposition modelling (FDM) is an AM technology based on an extrusion process of fabricating parts. This layer-by-layer method results in a poor surface finish, and as a result, manual finishing is often required, which consequentially reduces the definition of the geometrical features. This research proposes a novel way of achieving high surface finishing by using additive and finishing processes, followed by a physical vapor deposition (PVD) coating. Two test pieces were produced, the first one was subjected to computer numerical controlled (CNC) mechanical grinding with appropriate grades of grindstones; the second one was subjected to microsandblasting to remove excess material and the stair-stepping effect. Both test pieces were then subjected to a PVD coating process to provide a metal thin film. To benchmark the test pieces, the authors used a coordinate measure machine for dimensions and a roughness meter to verify the effectiveness of this postprocessing approach.